2006
DOI: 10.1111/j.1365-2494.2006.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

A simple statistical model for predicting herbage production from permanent grassland

Abstract: The considerable year-to-year and seasonal variation in grassland production is of major importance to dairy farmers in Europe, as production systems must allow for the risk of unfavourable weather conditions. A large portion of the variability is caused by weather and its interaction with soil conditions and grassland management. The present study takes advantage of the interactions between weather, soil conditions and grassland management to derive a reliable grassland statistical model (GRAM) for grasslands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…The determination coefficients were higher than what was reported in related studies for rangelands in Asia by Suzuki et al (2012) and Li Jianlong and Quangong (1998). In Australia, an estimation model by Trnka et al (2006) explained 78% variability in harvested herbage DM production. Results from stepwise regression analysis with harvested DM yield indicated that grass cover measurements alone could explain 73% of herbage DM yield.…”
Section: Discussioncontrasting
confidence: 79%
“…The determination coefficients were higher than what was reported in related studies for rangelands in Asia by Suzuki et al (2012) and Li Jianlong and Quangong (1998). In Australia, an estimation model by Trnka et al (2006) explained 78% variability in harvested herbage DM production. Results from stepwise regression analysis with harvested DM yield indicated that grass cover measurements alone could explain 73% of herbage DM yield.…”
Section: Discussioncontrasting
confidence: 79%
“…There is a paucity of published work with which to compare these results. Trnka et al (2006) compiled long-term (20 years) annualised pasture (predominantly perennial ryegrass) yield from three sites in Austria. Mean annual DM yield for pasture cut three times through the season with approximately 30 kg N applied after each cut was 9.4, 8.2 and 7.3 t/ha with minimum and maximum annual DM production in the range 7.4Á12.3, 4.7Á12.5 and 5.9Á8.8 t/ha, respectively for the three sites, equating to a difference of 49Á 165%, similar to the worst and best producing individual paddocks in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…While this framework is often applied in economic forecast analysis (e.g., Theil 1961Theil , 1966Clements and Frenkel 1980;Pindyck and Rubinfeld 1981), its statistical applicability is broader among other fields (Trnka et al 2006). Theil's inequality coefficient is defined as…”
Section: Pbl Schemes For Southeastern Us Cold Season Severe Weathermentioning
confidence: 99%